Structure of water masses in the archipelago Argentine Islands - I. P. Neverovsky; Y. I. Popov; V. N Sytov; A. S. Matygin (Ukrainian Antarctic Journal, 2015)
The structure of the water masses in the region of the archipelago Argentine islands was investigated according to the data oceanographic survey. The survey consisted of 60 stations of inter-island zone archipelago and three orthogonal cuts (10-12 stations) in the deep Straits of Penola. The two-layer vertical structure with desalinated water and warm surface layer and salty and cold water of bottom layer was observed in the area of inter-island. The thermocline is located at depths of 20-30 m in the northern and southern parts of the island area. The thermocline is located at a depth of 30-40 m in a more shallow central part of the island area, because there existed favorable conditions for spring-summer warming. Analysis of form T, S-curves allows to conclude that the monitoring space-time structure of the thermohaline field interisland the waters area enough make in a single point. The outlet glaciers of the Antarctic Peninsula in the summer generate large volumes of meltwater and create conditions for the formation of a three-layer structure of water. Cold intermediate layer separates relatively warm and more salty deep-water from warmed and freshened in summer conditions of surface waters. Analysis of T, S-diagrams of water of different regions of the western shelf of the Antarctic Peninsula led to the conclusion of a transfer of intermediate and deep waters from the south.